J.S. Marais, a great South African historian: a personal re-assessment. (2nd January 2016) - Garson, N.G.
ABSTRACT: This article is a personal assessment aimed to establish J.S. Marais's legacy. It is written in the light of the insights I gained as I interacted with him as an undergraduate and honours student (starting in 1949), as a research student, and finally as a departmental colleague over a period of ten years or so. It begins with my experience of his teaching. He was a poor lecturer, especially to large classes. This improved with smaller classes. He came into his own in the honours year. He was a specialist in South African history as a case study in the colonial era, from the seventeenth to the nineteenth century. Marais was excellent as a supervisor of postgraduate research from honours to doctoral level, empathetic and patient in handling his students' needs. A further feature of his honours teaching was his development of a course in historical method and philosophy of history. Next, the article covers Marais's preparation for an academic career, first at UCT and then at Oxford, leading in both cases to BA and honours degrees. Then his studies culminated in his doctoral thesis on the colonisation of New Zealand. This enabled him by 1927 to become a lecturer at UCT, a post he held until he moved to Wits as a senior lecturer in 1937. Marais's high reputation rested mainly on his books. The article continues with an assessment of each of these, including their reception by his colleagues. The article ends with an appraisal of Marais's qualities. Poor as an administrator, he was outstanding as a head of department at the intellectual level and also as a leader of the joint campaign of the University of the Witwatersrand (Wits) and UCT against the imposition of apartheid on the universities.